2012
DOI: 10.1002/jip.1362
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Hypothesis Confirmation Behaviors in a Simulated Murder Investigation: Implications for Practice

Abstract: Investigators have been shown to be prone to accessing information that confirms their preferred hypothesis. This tendency has been termed hypothesis confirmation. Hypothesis confirmation behaviour was explored in two studies using a computer administered simulation of a murder investigation. In Study 1, hypothesis confirmation behaviour did not differentiate successful and unsuccessful participants. However, unsuccessful participants stored more confirmatory information than non‐confirmatory information. Succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…If an analysis of this trace results in a database‐match, this person could be wrongfully accused of the crime and remain the main suspect within the investigation. After all, literature shows that once an idea is formed, people have difficulty changing it (Nickerson, ), and several studies have shown that investigators are prone to confirmation bias and belief perseverance and look for confirming evidence of their initial idea (Ask & Granhag, ; Rassin, Eerland, & Kuijpers, ; Wastell, Weeks, Wearing, & Duncan, ). This study showed that CSIs also have the tendency to look for confirmation rather than falsification.…”
Section: Discussionmentioning
confidence: 99%
“…If an analysis of this trace results in a database‐match, this person could be wrongfully accused of the crime and remain the main suspect within the investigation. After all, literature shows that once an idea is formed, people have difficulty changing it (Nickerson, ), and several studies have shown that investigators are prone to confirmation bias and belief perseverance and look for confirming evidence of their initial idea (Ask & Granhag, ; Rassin, Eerland, & Kuijpers, ; Wastell, Weeks, Wearing, & Duncan, ). This study showed that CSIs also have the tendency to look for confirmation rather than falsification.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fictional case files containing a description of a crime, a police report and a set of evidence implicating one or more suspects is an established method for examining decision making in the context of complex evidence (Ask & Granhag, 2007;O'Brien, 2009;Wastell, Weeks, Wearing, & Duncan, 2012b). This method allows the examination of how various factors may influence the final judgment produced, such as evidence presented, time allowed for decision production, and commitment to a decision option (Ask & Granhag, 2007;O'Brien, 2009;Simon et al, 2004).…”
Section: Fictional Crime Vignettes and Garden Path Methodologymentioning
confidence: 99%
“…This limitation meant that any individual preference for facts and possibly different stories was not able to be tested. However, Wastell et al (2012b) did facilitate such individual evidence accumulation and found that a majority of participants were more inclined to select information consistent with their initial preference than to suspend judgment for any length of time. Participants in Wastell et al's experiment also exhibited information selection behaviour consistent with argument theory.…”
Section: Limitationsmentioning
confidence: 99%
“…stress or time constraints; Evans 2006). When making decisions in high-stress/high-cognitive load situations, individuals are more likely to come to their conclusions quickly and use very little of the information available to them (Keinan 1987;Trippas et al 2013;Wastell et al 2012). Belief-based decisions under pressure occur because the likelihood of evaluating all available information is reduced (Rassin et al 2008).…”
Section: Beliefsmentioning
confidence: 99%